PELATIHAN PENGINPUTAN NILAI MENGGUNAKAN MICROSOFT ACCESS DI TK (TAMAN KANAK-KANAK) ABA 5 MATARAM: THE TRAINING VALUES INPUT USING MICROSOFT ACCES AT TK (TAMAN KANAK-KANAK) ABA 5 MATARAM - animah animah; Elin Elin Erlina Sasanti; Wirawan Wirawan Suhaedi (Buletin SWIMP, 2023)
In today's digital era, technological progress is a very influential part of the continuity of work in an institution or entering administrative work. Administrative work will be easier and more efficient by utilizing technology. Teachers have duties besides teaching their students as well as carrying out administrative roles, one of which is giving grades to students at the end of each semester. The values ​​included in the report card consist of several components, including daily scores including skills in dancing, singing, communicating, drawing, etc. The process of recording these values ​​requires time and accuracy from a teacher, therefore Microsoft Access is very helpful in managing student grades, thereby reducing processing time in the final assessment for report cards. The purpose of this service is to provide counseling and training regarding Microsoft access. The implementation of this service is divided into two stages, the first is counseling and the second is training. Microsoft access counseling and training was attended by staff and teachers of TK Aisyiyah Busthanul Athfal 5 Mataram. As a result of this community service activity, the participants not only understand how to operate Microsoft access but are also able to apply it in inputting student grades.